Pengaruh Spiritualitas Di Tempat Kerja Terhadap Komitmen Kerja Di Maha Vihara Maitreya, Medan - Carolina Catherine; Cindy Cindy; Williny Williny; William Vincent; Fauzi A.M. Hutabarat (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The background of this research is the author's interest in knowing the effect of spirituality in the workplace on work commitment at Maha Vihara Maitreya, Medan. The purpose of this study was to determine the effect of spirituality in the workplace on employee work commitment. This research uses associative quantitative method. This research is supported by the distribution of questionnaires to respondents. The sample of this research is Maha Vihara Maitreya employees, totaling 60 employees. The sampling technique used is a saturated sampling technique. The results of the normality test for spirituality in the workplace are 0.072 and work commitment is 0.064 where the value is greater than the standard significant = 0.05, so it can be concluded that the data tested are normally distributed. The results of the linearity test showed that between spirituality at work and work commitment had a linear relationship with a significance of 0.000. The results of the correlation between spirituality at work with a strong work commitment with the results of 0.764. The results of the determination coefficient test that the spirituality variable at work affects the work commitment variable by 58.4% while 41.6% is influenced by other factors. The result of simple linear regression is Y = (-14,584) + 1,234 X, which means that every increase or increase of 1 unit of spirituality will increase work commitment by 1,234 times. The results of hypothesis testing the calculated T value of 8.95 and obtained the T table value of 2.001. Where T count > T table (8.95 > 2.001), then Ho is rejected. Ha is accepted, which means that spirituality at work affects work commitment at Maha Vihara Maitreya, Medan. Thus it can be concluded that "Spirituality in the Workplace has an effect on Work Commitment at Maha Vihara Maitreya".